A study of food aid leakage in Bangladesh - Ahmed, Akhter; Rashid, Shahidur; Sharma, Manohar; Zohir, Sajjad (International Food Policy Research Institute, 2004)
The estimated average leakage in the Vulnerable Group Development (VGD) programme due to short ration and undercoverage is 8 percent of the total wheat allotment. These losses are low by international and Bangladesh standards, and are due, in part, to monitoring and evaluation throughout the system and women's empowerment at the union level to hold programme managers accountable." -- from Text